A Combination Design of Bag, Chair, Charger, Tables Made with Hazardous Waste Raw Materials in Tackling Environmental Pollution in the 4.0 Revolution Era - Muhamad Fadilah Fatah; Melyndo Ari Oftariano; Taksulanapurusa Zakly Setiabudi; Eko Sri Haryanto (Pendhapa, 2020)
The design of bags, chairs, chargers and tables is intended for commuter workers who carry out mobility activities every day. Design works that help to support commuter worker activities use a multi-functional system. The multi-function system is indicate by the shape and features attached. This product design method uses several stages including; 1) problem identification; 2) literature study: 3) design sketches, and: 4) design. The design results are turned into chairs, tables for lesehan (sitting on the floor) and bags. In addition, the other things are the storage box to store equipments for commuter workers while doing mobility and a solar cell which functions to capture sunlight which will be converted into electrical energy for energy sources to charge cellphones. Design works can be used in accordance with their respective functions. Design works carry the principle of multifunction, easy use, strong, lightweight and flexible. It is hoped that the design for this multi-functional products can be practical in use in the development of creative industries, and can overcome environmental pollution problems. From a theoretical perspective, it can be a reference for academics and science.